ANALYSIS OF THE ROLE OF LEADERSHIP IN HUMAN RESOURCE MANAGEMENT AT PT. KHANSA TOUR & TRAVEL SERANG - Suflani, Suflani (Yayasan Education and Social Center, 2024)
This study aims to analyze the role of leadership in human resource management (HRM) at PT. Khansa Tour & Travel Serang. Using a qualitative approach with a case study method, data were collected through in-depth interviews, observations, and documentation. The results indicate that transformational and situational leadership play a crucial role in enhancing employee motivation, productivity, and loyalty. Leaders who provide inspiration and support create a conducive work environment for employee development. However, challenges faced by the company include high turnover rates, low adaptation to digital technology, and differences in work styles across generations. Compared to previous studies, these findings suggest that flexible and innovative leadership can enhance HRM effectiveness. Therefore, the company is advised to adopt more adaptive leadership strategies, strengthen digital transformation, and improve employee well-being to maintain competitiveness in the tourism industry